Impaired apoptotic clearance and clonal deletion: onset or manifestation of Systemic Lupus Erythematosus? - Vaidyanathan, L; Bharadwaj, S (Medwin Publishers, 2017)
Systemic Lupus Erythematosus (SLE) is a prevalent widespread autoimmune disease where patients present numerous systemic manifestations like rashes, ulcers, hemolytic anemia, fever, thrombocytopenia, lymphadenopathy, and seizures. Although the disease is multifactorial in nature, this article aims to review the involvement of apoptotic pathways with SLE and to figure out if the pathways are instrumental to the onset or to the manifestation of the disease. It was found that impaired apoptotic pathways contributing to SLE included delayed apoptotic clearance and production of hyperactive B cells due to evasion of clonal deletion in the B cell development pathways. After thorough and detailed analysis, it was concluded that the contribution of the apoptotic pathways towards onset may be in the context of autoreactive B cell formation while incomplete apoptotic clearance being associated with the clinical manifestation of the disease.